Gender differences in the recognition of emotional faces: are men less efficient? - Ana Ruiz-Ibáñez; José T. Boyano (Interacciones)
As research in recollection of stimuli with emotional valence indicates, emotions influence memory. Many studies in face and emotional facial expression recognition have focused on age (young and old people) and gender-associated (men and women) differences. Nevertheless, this kind of studies has produced contradictory results, because of that, it would be necessary to study gender involvement in depth. The main objective of our research consists of analyzing the differences in image recognition using faces with emotional facial expressions between two groups composed by university students aged 18-30. The first group is constituted by men and the second one by women. The results showed statistically significant differences in face corrected recognition (hit rate - false alarm rate): the women demonstrated a better recognition than the men. However, other analyzed variables as time or efficiency do not provide conclusive results. Furthermore, a significant negative correlation between the time used and the efficiency when doing the task was found in the male group. This information reinforces not only the hypothesis of gender difference in face recognition, in favor of women, but also these ones that suggest a different cognitive processing of facial stimuli in both sexes. Finally, we argue the necessity of a greater research related to variables as age or sociocultural level.